Hybrid Intelligent Optimization Technique (HIOT) Driven FOPID Controller for Load Frequency Control of Deregulated Power System - Pandey R.K.; Gupta D.K.; Dei G. (My University, 2025)
This paper presents the novel concept to deal with frequency and tie-line control for multi-source multi-area hybrid power systems in a deregulated environment. The test system that operates under deregulated regime has various sources such as thermal power plants, hydroelectric systems, wind energy sources, and gas turbine-based power plants. The reported work mainly focuses on effectively minimizing the variations in frequency, tie-line, and area control error with various operational shifts. Since the regulation of frequency is essential for system stability, therefore proper tuning of Fractional Order PID (FOPID) controllers is very important in order to have oscillation damping. To overcome the disadvantage of conventional controllers in load frequency control (LFC), a hybrid intelligent algorithm has implemented to tune the controller gains of FOPID controllers by minimizing ITAE as an objective function. The proposed intelligent technique utilizes the main features of Gravitational Search Algorithm (GSA), Firefly Algorithm (FA), and Particle Swarm Optimization (PSO) techniques. Simulations are carried out for multi-source multi-area systems under deregulated environment with different power agreements and load change scenarios. © 2022 IEEE.